Seismic Expression of Some Geological Features of Andaman-Offshore West Sumatra Subduction zone - Herman Darman (Berita Sedimentologi, 2011)
A subduction zone developed in the south of Myanmar, continued to the Andaman Sea (India), west of Sumatra and south of Java (Indonesia). Two major fault system developed parallel to the subduction zone, so called the Mentawai Fault System and Sumatra Fault system. To the north, where the subduction zone changes its orientation from NNW-SSE to NS, a spreading zone developed towards the east of Andaman Sea. This zone is a complex and active geological system. The 2004 Aceh Tsunami was a major disaster which was triggered in this subduction zone.The Andaman - Offshore West Sumatra subduction system is where part of the Indo-Australian oceanic plate moving northwards and going beneath the southern tip of Eurasian continental plate. Sumatra Island, which is part of Indonesian volcanic island arc, occurs parallel to and inland from the boundary between these two plates. An accretionary prism or wedge has formed from sediments that accreted onto the nonsubducting plate. Most of the material in this wedge consists of marine sediments scraped off from the downgoing slab of Indian oceanic plate with some erosional products of Sumatra volcanics. Fore-arc ridge in this system is a chain of islands (e.g. Andaman, Simeulue, Nias, Mentawai, and Enggano), formed by the accretionary wedge. A series of fore-arc basins developed between the accretionary ridge and the volcanic arc.This region is also an active petroleum exploration area. Recently, there are a number of companies (e.g. Spectrum, TGS and Geco) that provide new and reprocessed seismic lines to the market. These seismic lines show the geological features in this subduction system.